Get To Know The History And Function Of The West Javanese Angklung Musical Instrument - Awaloedin, Dipa Teruna; Pradini, Gagih; Agustiani, Fitri; Hibatullah, Muhammad Rafif; Azzahra, Lintang Salwa; Putri, Ananda Amelia (CV ODIS, 2024)
West Java is a collection of various types of very beautiful nature with enchanting cultural attractions. The diversity of existing cultures is shown through the diversity of arts that are staged. This art is an expression of human thoughts, feelings, and ideas that differ from their environment and experience. Along with the development of the times, the growing diversity of art created by humans, as well as various forms of types of works of art, Artworks are one of the cultural products of a nation, which is priceless. Angklung is a popular traditional musical instrument from West Java. Angklung musical instruments have been known by the Sundanese people since the royal era, and have grown in popularity since November 2010, when Angklung was listed as Masterpieces of the Oral and Intangible Heritage of Humanity by UNESCO.